2023
DOI: 10.1515/med-2023-0823
|View full text |Cite
|
Sign up to set email alerts
|

The progress of autoimmune hepatitis research and future challenges

Yang Zhang,
Dehe Zhang,
Ling Chen
et al.

Abstract: Autoimmune hepatitis (AIH) is a chronic liver inflammatory disease with various immune system manifestations, showing a global trend of increased prevalence. AIH is diagnosed through histological abnormalities, clinical manifestations, and biochemical indicators. The biochemical markers involve interfacial hepatitis, transaminase abnormalities, positive autoantibodies, etc. Although AIH pathogenesis is unclear, gene mutations and immunological factors could be the leading factors. AIH usually presents as a chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 178 publications
0
1
0
Order By: Relevance
“…Compared to the typical structures observed in healthy individuals, study has revealed modified intestinal tight junctions and inflammatory infiltrates within the lamina propria of AIH patients. These modifications result in damage to the intestinal mucosa and elevated levels of endotoxins in the bloodstream, thereby triggering the immune tolerance impairment mechanism and causing liver injury (Kharrazian et al, 2023;Zhang et al, 2023b;Zhu et al, 2023). Under normal physiological conditions, anaerobic/aerobic bacteria in the intestinal microbiota maintain a dynamic balance and participate in physiological processes, and the disruption of this balance also can lead to intestinal barrier damage and bacterial translocation across the intestinal barrier to other organs, resulting in inflammation, immune disorders, and various other adverse effects (Lin et al, 2015).…”
Section: Gut Microbialmentioning
confidence: 99%
“…Compared to the typical structures observed in healthy individuals, study has revealed modified intestinal tight junctions and inflammatory infiltrates within the lamina propria of AIH patients. These modifications result in damage to the intestinal mucosa and elevated levels of endotoxins in the bloodstream, thereby triggering the immune tolerance impairment mechanism and causing liver injury (Kharrazian et al, 2023;Zhang et al, 2023b;Zhu et al, 2023). Under normal physiological conditions, anaerobic/aerobic bacteria in the intestinal microbiota maintain a dynamic balance and participate in physiological processes, and the disruption of this balance also can lead to intestinal barrier damage and bacterial translocation across the intestinal barrier to other organs, resulting in inflammation, immune disorders, and various other adverse effects (Lin et al, 2015).…”
Section: Gut Microbialmentioning
confidence: 99%